2012
DOI: 10.1016/j.immuni.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Virus Recognition by Toll-7 Activates Antiviral Autophagy in Drosophila

Abstract: Innate immunity is highly conserved and relies on pattern recognition receptors (PRRs) such as Toll-like receptors (identified through their homology to Drosophila Toll) for pathogen recognition. While Drosophila Toll is vital for immune recognition and defense, roles for the other eight Drosophila Tolls in immunity have remained elusive. Here we have shown that Toll-7 is a PRR both in vitro and in adult flies; loss of Toll-7 led to increased Vesicular Stomatitis virus (VSV) replication and mortality. Toll-7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
211
2
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(219 citation statements)
references
References 62 publications
4
211
2
2
Order By: Relevance
“…Other pathogen sensors (such as TLR3, TLR4, TLR7, TLR8 and NOD2) are also known to induce autophagy upon binding with their specific ligand, via a MyD88 independent pathway (reviewed by Richetta & Faure, 2013). Autophagy is also an antiviral mechanism utilized by arthropods (Nakamoto et al, 2012). In Drosophila, Toll-7 recognizes vesicular stomatitis virus (VSV) at the plasma membrane and induces antiviral autophagy via an NF-kB-independent pathway (Nakamoto et al, 2012).…”
Section: Programmed Cell Death (Pcd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other pathogen sensors (such as TLR3, TLR4, TLR7, TLR8 and NOD2) are also known to induce autophagy upon binding with their specific ligand, via a MyD88 independent pathway (reviewed by Richetta & Faure, 2013). Autophagy is also an antiviral mechanism utilized by arthropods (Nakamoto et al, 2012). In Drosophila, Toll-7 recognizes vesicular stomatitis virus (VSV) at the plasma membrane and induces antiviral autophagy via an NF-kB-independent pathway (Nakamoto et al, 2012).…”
Section: Programmed Cell Death (Pcd)mentioning
confidence: 99%
“…Autophagy is also an antiviral mechanism utilized by arthropods (Nakamoto et al, 2012). In Drosophila, Toll-7 recognizes vesicular stomatitis virus (VSV) at the plasma membrane and induces antiviral autophagy via an NF-kB-independent pathway (Nakamoto et al, 2012). …”
Section: Programmed Cell Death (Pcd)mentioning
confidence: 99%
“…RNAi in Drosophila cells is robust, and conserved immune biology with humans has been demonstrated (e.g., Toll) (Lemaitre et al 1996), suggesting that we can use Drosophila to probe both insect and human antiviral factors (Cherry 2005;Hao et al 2008;Sabin et al 2009;Sessions et al 2009;Moser et al 2010;Rose et al 2011). Furthermore, Drosophila has been used as a model to study arboviral infection, including RVFV (Sabin et al 2009;Sessions et al 2009;Filone et al 2010;Moser et al 2010;Rose et al 2011;Nakamoto et al 2012). …”
mentioning
confidence: 99%
“…In Drosophila, Spätzle is a ligand for Toll during both embryogenesis and AMP induction but the up-stream events that finally lead to cleavage of pro-Spätzle into Spätzle differ (Morisato and Anderson, 1995; Lemaitre et al, 1996). However, in one recent study the direct binding of an arbovirus to the Drosophila Toll-7 receptor was demonstrated (Nakamoto et al, 2012). Caution must therefore be exercised when assigning a function for newly discovered TLRs in different phyla.…”
Section: Tlrs In Invertebratesmentioning
confidence: 99%